FAKTOR-FAKTOR YANG MEMPENGARUHI ALIH FUNGSI LAHAN PERTANIAN KE SEKTOR NON PERTANIAN DI DAERAH ISTIMEWA YOGYAKARTA - SUSI WURI ANI (Universitas Sebelas Maret, 2009)
The objective of this research were to calculate the rate of the agriculture land conversion and the determinants of the agriculture land conversion in Yogyakarta.